Developing PTS Device (pH, TDS, and Salinity) to Determine the Water Quality for Cultivating Milkfish (Chanos chanos Forsk) in Pati District - Fina Fakhriyah; Putut Marwoto; Edy Cahyono; Retno Sri Iswari (Jurnal Penelitian Pendidikan IPA, 2022)
The importance of water management for milkfish cultivation determines the yields. This research aims to find the performance specification and pH, TDS, and Salinometer measurement (PTS) design validity and relevance. These tools are combinations from various sensors connected by Arduino nano 328 system, pH meter analogue, turbidity, and salinity measurement sensors complemented by Liquid Crystal Display and battery. They are connected by data cable. The findings showed that 1) the systemâ€™s performance specification was applying copper electrodes as the salinity, turbidity, and pH meter sensors. The Arduino system did the readings of the data. 2) the device-design specification was valid and relevant to measure the pond water quality for cultivating milkfish (Chanos chanos Forsk).Â